Actor Analysis In Sustainable Village-Based Enterprises: Examining The Role Of Stakeholders - M. Rudi Irwansyah; Bagus Shandy Narmaditya; Diota Prameswari Vijaya (Universitas Udayana, 2024)
Fundamentally, the establishment of village-based enterprises is a mandate of the village law inan effort to encourage or stimulate the wheels of the rural economy and also increase villageincome sources. The implementation of the mandate of this law makes it important to involveVillage-Based Enterprises stakeholders in its management. This study aims to determine theroles and interaction patterns of stakeholders (actors) in the management of village-basedenterprises in Bali. The analysis method used in this study is Mactor. Primary data collectionwas obtained through interviews guided by a questionnaire and direct observation. The researchfindings indicate that each player, specifically the Village Ministry PDTT, ProvincialGovernment, District Government, Village Government, Village-Based Enterprise Manager,Villagers, and Business Partners, play a crucial role in determining the sustainability of villagebased companies. The linkages between actors interact with each other in the management ofvillage-based enterprises and are able to mobilize actors to achieve management goals. All actorsagree that village-based enterprises must be developed both in terms of management andinstitutions. The contribution of the results of this research becomes a recommendation forcollaborative planning among stakeholders, so that it becomes a strategic step in sustainablevillage-based enterprise.